Validation of Spanish Version of the Spirituality and Spiritual Care Rating Scale (SSCRS‐Sp) in Nursing Professionals - M. D. Fernández‐Pascual; A. Reig‐Ferrer; L. Martínez‐Rodríguez; J. A. Quesada‐Rico; W. McSherry; L. Riquelme‐Ros (Nursing Open)
ABSTRACT Aim To examine the reliability and construct validity of the Spanish adaptation of the Spirituality and Spiritual Care Rating Scale (SSCRS) within the nursing professionals' context. Design Observational and descriptive cross‐sectional study. Methods The sample consisted of N = 325 nursing professionals from various healthcare settings, including hospitals, clinics and community healthcare centres. Following translation and cultural adaption of the SSCRS, the scale underwent psychometric assessment of its construct validity through exploratory and confirmatory factor analysis. Internal consistency analysis was also performed using a McDonald's omega. The reporting in this investigation adhered to the STROBE checklist. Results The exploratory factor analysis (EFA) revealed a two‐factor structure, with one factor closely aligning with one religiosity dimension and the other factor combining the spirituality, spiritual care and personalised care dimensions. The results of the confirmatory factor analysis did not provide an adequate fit to the data for both the two‐factor solution found in the EFA and the four‐factor solution proposed by McSherry, Draper, and Kendrick (2002). Even though the four‐factor solution showed a slightly better fit than the two‐factor solution, neither model achieved a satisfactory fit. The lack of formal education and confusion between religion and spirituality among healthcare professionals could have influenced the responses and interpretation of the results. Conclusion The findings showed that the SSCRS‐Sp demonstrated good internal consistency, indicating that the items in the scale are reliably measuring the targeted constructs. Further refinement and validation of the scale are needed to establish a robust factor structure in the target population. Relevance to Clinical Practice The SSCRS‐Sp can be used to assess the nurses' perceptions of spirituality and spiritual care. The availability of this tool represents a significant step towards greater integration of the spiritual dimension of care within a holistic nursing care framework in Spanish‐speaking countries. Patient or Public Contribution Nursing professionals responded to the research scale.